2013
DOI: 10.7763/ijiet.2013.v3.237
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Computer Science Students through Gamification in an Online Social Network Based Collaborative Learning Environment

Abstract: Gamification is the use of game mechanics such as rewarding points and achievement badges to engage target audience and encourage desired behaviors. Gamification has gained a great surge of interest in recent years as an effective approach to engage existing users and attract new users to web sites. In this paper, the use of gamification in engaging Computer Science students in an online social network based collaborative learning environment, called PeerSpace, is discussed. PeerSpace integrates a suite of Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 4 publications
2
48
0
7
Order By: Relevance
“…Twelve out of 19 studies reported a positive impact on student motivation as a result of gamification (Abramovich et al, 2013;Barata et al, 2013;Charles et al, 2011;deMarcos et al, 2014;Dominguez et al, 2013;Gåsland, 2011;Goehle, 2013;Li et al, 2013;McDaniel et al, 2012;Mekler et al, 2013a;Mekler et al, 2013b;O'Donovan et al, 2013). Elements of gamification such as points, badges, leaderboards and levels provide feedback and encouragement to learners.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve out of 19 studies reported a positive impact on student motivation as a result of gamification (Abramovich et al, 2013;Barata et al, 2013;Charles et al, 2011;deMarcos et al, 2014;Dominguez et al, 2013;Gåsland, 2011;Goehle, 2013;Li et al, 2013;McDaniel et al, 2012;Mekler et al, 2013a;Mekler et al, 2013b;O'Donovan et al, 2013). Elements of gamification such as points, badges, leaderboards and levels provide feedback and encouragement to learners.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, levels were reported in eight of 19 studies (Barata et al, 2013;Berkling & Thomas, 2013;Goehle, 2013;Li et al, 2013;Mayer & Johnson, 2010;Mekler et al, 2013b;Turner et al, 2013;Watson et al, 2013). To implement levels, users must gain points.…”
Section: Levelsmentioning
confidence: 99%
See 3 more Smart Citations